Bi-Directional Relationships Between Psychological Symptoms and Environmental Factors in Early Adolescence - Huang, Ziyan; Endo, Kaori; Yamasaki, Syudo; Fujikawa, Shinya; Ando, Shuntaro; Hiraiwa-Hasegawa, Mariko; Kasai, Kiyoto; Nishida, Atsushi; Koike, Shinsuke (Frontiers in Psychiatry, 2020)
Aim: Bi-directional relationships between various environmental factors and psychological symptoms can be seen from childhood to adolescence; however, there has been little prospective cohort study which investigated the relationships simultaneously. In this study, we first distinguished specific psychological symptoms from general psychopathology using bifactor modeling and then tested the relationships between psychological symptoms and environmental factors from childhood to early adolescence using a structural equation model (SEM). Methods: The analyses were based on Tokyo TEEN Cohort (TTC) data collected between October 2012 and March 2016. We obtained self-reported psychological symptoms and environmental factors from both parents and children (at their ages of 10 and 12). Participants were 3,171 children aged 10 (girls = 1,487 (46.9%), mean age, SD = 10.2, 0.28) and subsequently 12 (N=3,007, follow-up rate 94.8%, mean age, SD = 12.2, 0.31) from three municipalities in Tokyo area. Results: The best-fit symptom models included 4 unique factors as well as general psychopathology as the common factor. Combining the good fit bifactor model and the SEM, positive relationships between symptoms and environmental factors at the same waves and some bi-directional relationships were found. Especially, general psychopathology at age 10 was associated with bullying at age 12 and parental depressive symptoms at age 10 with general psychopathology at age 12. However, some negative relationships such as bullying/bullied involvement and later psychological symptoms were also seen. Conclusion: By using the newly introduced methodology, our results were partly consistent with previous literature. Further studies are needed to validate this methodology and accelerate the findings regarding the emergence of psychological symptoms and the impact of environmental factors from childhood to early adolescence.